2015
DOI: 10.1007/s00405-015-3500-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-sialendoscopy ductoplasty by salivary duct stent placements

Abstract: With damage to a duct or papilla after sialendoscopy, a stent may be necessary to prevent re-stenosis and for maintaining the salivary duct open after complete sialendoscopy. However factors affecting outcomes and complications after stent placement remain unclear. This study aimed to report preliminary experiences in salivary duct stent placement after sialendoscopy. Data from 35 procedures in 33 patients who received sialendoscopy with salivary duct stent placements at Mackay Memorial Hospital between Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Stents can be useful in the prevention of restenosis after the dilatation of ductal strictures or to avoid a papillary stenosis and secondary iatrogenic obstruction after papillotomy. Stent placements may also be helpful in the regeneration of ductal defects and in keeping a wide luminal diameter after the ductal walls are primarily closed from incision 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Stents can be useful in the prevention of restenosis after the dilatation of ductal strictures or to avoid a papillary stenosis and secondary iatrogenic obstruction after papillotomy. Stent placements may also be helpful in the regeneration of ductal defects and in keeping a wide luminal diameter after the ductal walls are primarily closed from incision 17 .…”
Section: Methodsmentioning
confidence: 99%
“…For the stent placement, the hypospadias silastic stent tubes, pediatric feeding tubes and epidural catheter were used in many cases. [11,12] Many researchers reported different duration times for stent placement. [11] We used an intravenouos cannula for 3 days.…”
Section: )mentioning
confidence: 99%
“…[11,12] Many researchers reported different duration times for stent placement. [11] We used an intravenouos cannula for 3 days. At the 1 year follow-up of the cases, there were no complication and it was seen that the ducts' orifices were open and there were no abnormalities of the secretory functions.…”
Section: )mentioning
confidence: 99%
“…In cases where ductal stenosis has occurred, salivary duct stent placement appears to be one of the main treatment options (2,3). A previous study demonstrated that salivary duct stent placement using hypospadias silastic and pediatric feeding tubes (size 5-Fr) was successfully achieved and maintained for approximately two weeks before displacement (4). Although stenting is routinely used in clinical practice, a common limitation associated with ductal stents is the relatively short duration of stent implantation following surgery.…”
Section: Introductionmentioning
confidence: 99%